Enormous Ganges-Brahmaputra sediment discharge during strengthened early Holocene monsoon - Goodbred, S. L., Jr.; Kuehl, S. A. (Geology, 2000)
Rivers are the main source of terrigenous sediment delivered to continental margins and thus exert a major control on coastal evolution and sequence development. However, little is known about past changes in fluvial sediment loads despite the recognition of significant variation under changing climatic regimes. In this study we present the first quantified estimate of sediment discharge for a major river system under conditions of an intensified early Holocene monsoon. Development of the Ganges-Brahmaputra River delta began ca. 11000 yr B.P., when rising sea level flooded the Bengal basin, thereby trapping most of the river's discharge on the inner margin. Chronostratigraphic data from these deltaic deposits are used to calculate the rates of sediment storage on the margin, which provide a minimum estimate of the river's past sediment load. Results reveal that ∼5 × 1012 m3 of sediment was stored in the Bengal basin from ca. 11000 to 7000 yr B.P., which corresponds to a mean load of 2.3 × 109 t/yr. In comparison, modern sediment load of the Ganges-Brahmaputra is ∼1 × 109 t/yr, ranking it first among the world's rivers and underscoring the significance of a two-fold increase sustained over 4 k.y. Furthermore, the timing of immense discharge in the early Holocene strongly suggests its relation to a stronger than present southwest monsoon in South Asia. Similar patterns of high monsoon-related sediment discharge have been noted throughout the tropics and subtropics, suggesting a widespread fluviosedimentary response, the potential magnitude of which is showcased by the Ganges-Brahmaputra system.
id: 147